Pengembangan Aplikasi Literature Sebagai Media Peningkatan Literasi di SD Negeri Gombang - Ramadhanie, Bella; Rohmah, Lely Arbiati Nur; Putri, Nadia Maharani; Oktaviani, Tristine; Kintoko (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The Community Service Student Creativity Program (PKM-PM) aims to produce learning media applications. The resulting application is in the form of developing a Literature application as a medium for increasing literacy. The methods of community service carried out during the program are Observing Partners' Conditions (Conditions, Problems, Needs), Designing and Developing Literary Applications, Socializing the Use of Literary Applications, Assistance in Using Literary Applications, and Evaluation and Testimonials. The results of program implementation show that the media developed is suitable for use. Product trial on 21 Gombang State Elementary School students who showed approval for the use of this media in learning. This learning media makes learning more interesting and varied so that students become interested and active in learning about fantasy stories.